Early Primary Biliary Cirrhosis: A New Association with Erythema Nodosum of Unknown Origin - Gatselis, Nikolaos K. (Hindawi Publishing Corporation, 2010)
Primary biliary cirrhosis (PBC) is associated with immune-mediated dermatologic disorders. The association of PBC with erythema nodosum (EN) seems rare. We report two females (42 and 44 years old) with low-grade fever, arthralgias, and elevated cholestatic enzymes in the first and fatigue in the second. Patients were also suffering from typical EN lesions characterized by multiple erythematous, painful nodules over the anterior portions of their lower extremities. Clinical and extensive laboratory work up excluded all known EN causes. PBC diagnosis was established according to the cholestatic biochemical profile, anti-mitochondrial antibodies (AMA) positivity and liver histology (first), and AMA and antinuclear (ANA) PBC-specific antibodies (second). Our report may suggest that PBC could be kept in mind in EN patients of unknown aetiology and particularly, when middle-aged female patients are affected. In such cases a thorough evaluation for AMA and/or ANA PBC-specific antibodies could be helpful to achieve a correct and timely diagnosis.